Steroids Produced by Endophytic Fungi (Fusarium phaseoli) Isolated from Chisocheton macrophyllus and their Antibacterial Activity against Escherichia coli and Staphylococcus aureuss - Katja, Dewa Gede; Sari, Aprilia Permata; Sinaga, Siska Elisahbet; Nurlelasari, Nurlelasari; Farabi, Kindi; Sofian, Ferry Ferdiansyah; Fajriah, Sofa; Naini, Al Arofatus; Supratman, Unang (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Steroids are secondary metabolic derivatives of terpenes containing the tetracyclic ring system known to exhibit fascinating pharmacological activity. Steroids are distributed in various genera of endophytic fungi including Fusarium genus which lives inside a higher tree such as Chisocheton macrophyllus. The purpose of this research is to identify and characterize the chemical structure of steroids generated by F. phaseoli, an endophytic fungus obtained from C. macrophyllus roots, as well as to assess their antibacterial activity against Escherichia coli and Staphylococcus aureus. The brown rice medium was fermented with F. phaseoli for six weeks before extraction with ethyl acetate. The extracts yielded four compounds, identified using spectroscopic methods such as FTIR, HRTOF-MS, 1D, and 2D NMR, and then compared to previously described compounds. Compounds 1-4 were identified as ergosterol (1), ergosterol peroxide (2), atroside (3), and cerevisterol (4). The four isolated compounds were evaluated for antibacterial activity against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 11229 and displayed activity with MIC50 values of 500 µg/mL. Keywords: Antibacterial activity; Chisocheton macrophyllus; Fusarium phaseoli; steroids.